Removal efficiency and potential risks of steroid estrogens in selected wastewater treatment plants in the Klang Valley, Malaysia - Ting, Yien Fang (2019)
Wastewater treatment plant (WWTP) is the major source for steroid estrogens loaded into aquatic environment because wastewater treatment systems are generally designed to remove basic wastewater parameters. Amongst steroid estrogens, natural 17β- estradiol (E2) and synthetic 17α-ethinylestradiol (EE2) are potent in estrogenic potency and have been classified as “Watch List” in Directive 2013/39/EU. The general objective of the study is to analyze the occurrence, removal, and potential risks of natural E2 and synthetic EE2 in six selected WWTPs located in Klang Valley. The specific objectives of the study are: (1) to determine natural E2 and synthetic EE2 concentrations and wastewater physicochemical parameters in influent and effluent, (2) to identify the influence of socio-demographic profile on natural E2 and synthetic EE2 concentration in influent, (3) to evaluate the removal efficiency of natural E2 and synthetic EE2 in WWTP, (4) to analyze relationship between wastewater physicochemical parameters associated with natural E2 and synthetic EE2 removal in WWTP, and (5) to assess the potential risks of natural E2 and synthetic EE2 to human and aquatic environment. Wastewater samples were collected bimonthly for a period of six months (from March to July 2016) from influent and effluent of six selected WWTPs located in Klang Valley. The wastewater samples were analyzed using 17β- estradiol and 17α-ethynylestradiol ELISA kit. Kruskal-Wallis test and principal component analysis (PCA) were used for statistical analysis. Risk quotient (RQ) was applied for human risk while mathematical models such as estradiol equivalent concentration (EEQ) and concentration addition (CA) models were applied for aquatic environment risk. Quantitative results showed natural E2 concentration was 88.17±7.03 ng/L to 93.93±6.91 ng/L in influent and 35.10±17.33 ng/L to 85.20±7.54 ng/L in effluent. Synthetic EE2 concentration was 0.22±0.21 ng/L to 4.94±6.32 ng/L in influent and 0.02±0.02 ng/L to 1.04±0.77 ng/L in effluent. For wastewater physicochemical parameters, total suspended solid was 95.17±3.96 mg/L to 129.80±4.95 mg/L in influent and 2.84±0.95 mg/L to 14.67±0.57 mg/L in effluent, pH was 6.73±0.01 to 7.04±0.03 in influent and 6.79±0.06 to 6.95±0.02 in effluent, oxidation reduction potential was -29.20±3.20 mV to -18.07±1.93 mV in influent and 5.37±3.25 mV to 16.77±3.93 mV in effluent, and temperature was 32.20±0.1°C to 35.60±2.31°C in influent and 32.47±0.12°C to 34.63±0.67°C in effluent. Kruskal-Wallis test indicated significant difference between natural E2, synthetic EE2 concentrations in influent and socio-demographic profile (gender, marital status, education, and household). The removal efficiency was 6.4% to 63.0% for natural E2 and 28.3% to 99.3% for synthetic EE2. The PCA indicated wastewater physicochemical parameters were associated significantly with natural E2 and synthetic EE2 removal efficiency in WWTP. For human risk, cumulative RQ value was below the allowable limit, except WWTP 1. For aquatic environment risk, EEQ model predicted estrogenic activity of 35.1 EEQ-ng/L to 85.3 EEQ-ng/L, while CA model predicted estrogenic activity of 105.4 ng/L. However, these estrogenic activity in aquatic environment could be lower due to dilution effect through rainfall. This study output is useful as baseline quantitative data of E2 and EE2 in Klang Valley WWTPs and its potential risks to human and aquatic environment.